Encouraging women's empowerment: a qualitative analysis on household food waste management in Bangladesh utilizing 5R approach - Sultana, Tahera; Rohaiza, Rohaiza; Syed Hussien, Sh Fatimah Alzahrah (Scholars Middle East Publishers, 2024)
Household food waste management (HFWM) poses a significant challenge in developing countries like Bangladesh due to diverse food waste types, inadequate policies, and rapid urbanization. This study investigates women's empowerment in Dhaka through the 5R approaches: Reduce, Reuse, Recycle, Repurpose, and Recover. By employing qualitative methods, including in-depth interviews and case studies with a purposive and snowball-sampled group of women, the research examines how the 5R strategies impact women's socio-economic empowerment. Findings reveal that educated women, especially those engaged in roof and balcony gardening, effectively implement the 5R approaches, notably composting kitchen waste. Women in owner-occupied homes demonstrate more comprehensive food waste management practices compared to those in rented houses. The study highlights that HFWM through the 5R approaches improves environmental sustainability and provides economic benefits, such as reducing reliance on chemical fertilizers and creating new employment opportunities. This research underscores the potential for women's active participation in HFWM to contribute to cost savings, fresh produce cultivation, and potential business ventures, thereby enhancing their social and economic status. The insights gained can inform future initiatives aimed at promoting environmental sustainability and gender equality in urban Bangladesh.